The Measurement of Managerial Performance on Service, Job Satisfaction, and Decision-Making Survey at The Jakarta Education Service - Pallawagau, Andi; Asyari; Ramli, Muhammad (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
By implementing the Performance Management system, each agency's performance will be assessed based on its output, not just based on budget absorption or the agency's financial predicate. outcomes whose benefits can be felt directly by the community and implemented effectively and efficiently. The bureaucracy ensures that activities financed by the state budget are effective and have a positive impact on achieving development targets. The object of this research is to analyze and know how the direct effect is between quality of services, job satisfaction, and Decision Making toward Managerial performance. This research used a quantitative method. The sample of this research at the Jakarta Education Service that took 90 employees. The sample used to use simple random sampling. Data was obtained by using a Likert scale questionnaire form. The research results illustrate that service quality has a significant positive effect on managerial performance, job satisfaction has a significant positive effect on managerial performance, and decision-making has a significant positive effect on managerial performance. The implications of the research results recommend that to improve managerial performance, good service capabilities are needed, and appropriate decision-making that meets the needs of the institution or organization and is based on budget achievements.